In vivo analgesic effect of aqueous extract of Tamarindus indica L. fruits. - Khalid, Syamimi; Shaik Mossadeq, Wan Mastura; Daud , Ahmad Israf; Hashim, Puziah; Rejab, S.; Shaberi, A.M.; Mohamad, Azam Shah; Zakaria, Zainul Amiruddin; Sulaiman, Mohd Roslan (Karger: Open Access Journals, 2010)
To study the effects of Tamarindus indica L. aqueous fruit extract on the antinociceptive activities in rodent models. Methods: The analgesic effect was evaluated using acetic acid-induced writhing, hot plate and formalin tests. Results: The extract (60–600 mg/kg) significantly (p < 0.05) inhibited the writhing test in a dose-dependent manner with the percentage of analgesia recorded between 51.8 and 74.1%. In addition, the extract also significantly (p < 0.05) increased the latency time in the hot plate test in a dose-dependent manner. Further study showed that the extract elicited inhibitory activity in both the early and late phases of the formalin test. Moreover, pretreatment with 5 mg/kg naloxone, a nonselective opioid receptor antagonist, significantly (p < 0.05) modified the antinociceptive effect of the extract in all tests. Conclusion: The aqueous extract of T. indica possesses potential antinociceptive activity at both the peripheral and central levels, which are mediated via activation of the opioidergic mechanism.